Machine Login Monitoring and Tracking Security System - Raj, Aiswarya; Manoharan, Meenu; Alex, Melbin; Prasad, Pravya; John, Majo (International Journal of Computer Sciences and Engineering, 2014)
Machine Login Monitoring and Tracking Security System (MLMTSS) were used to monitor all illegal and malicious attempts of the system user. The system should be able to provide a complete log of text entered such as passwords, emails send, websites visited. The user's login time was send by SMS to the admin. This system tracks all the keystrokes, processes opened and all operations performed by the user and send it through e-mail. The system takes screenshots within the specified interval of time and sends it with the tracked information to the administrator's mail. It also runs invisibly so that the person who is using the computer doesn't even have to be aware that it is running.